2013
DOI: 10.1136/annrheumdis-2013-eular.2105
|View full text |Cite
|
Sign up to set email alerts
|

SAT0380 Silent Osteonecrosis of the Femoral Head Following High-Dose Corticosteroids in Patients

Abstract: Background: Osteonecrosis (ON) is known to be one of the most disabling complications following corticosteroid (CS) medications. However, evidence regarding risk of asymptomatic prevalence of ON among different diseases and the impact of variable steroid regimens are conflicting. We aimed to determine the prevalence of ON of femoral head in asymptomatic patients with systemic rheumatic diseases who received high-dose CS and also clarify its relationship with different dosages and regimens. Methods: In this cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Our study showed higher prevalence of avascular necrosis in osteoporotic patients. Some studies in lupus patients treated with cytotoxic drugs and corticosteroids have been carried out, which have shown that the prevalence of asymptomatic avascular necrosis is high in these patients (8). One of the things that justifies the difference between our study and these studies, is that avascular necrosis can be caused by lupus in lupus patients.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our study showed higher prevalence of avascular necrosis in osteoporotic patients. Some studies in lupus patients treated with cytotoxic drugs and corticosteroids have been carried out, which have shown that the prevalence of asymptomatic avascular necrosis is high in these patients (8). One of the things that justifies the difference between our study and these studies, is that avascular necrosis can be caused by lupus in lupus patients.…”
Section: Discussionmentioning
confidence: 55%
“…These drugs put patients in risk of hip avascular necrosis (6,7). Some studies in patients using glucocorticoids and immunosuppressant drugs like lupus, show that risk of femoral head avascular necrosis is high (8). One of the reasons that prevalence of femoral head avascular necrosis is higher in these patients is the use of glucocorticoids (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of high-risk patients with periodic hip MRI would help diagnose necrosis in its early stage. [ 40 ] The radiologic features correspond to the underlying pathology. The typical change in T1 imaging is a single density line that represents the separation of the normal and necrotic bones, while that in T2 imaging with another high signal line represents the granulation tissue with an increased vascularity.…”
Section: Iagnosis and P Rognosismentioning
confidence: 99%
“…Meanwhile, it is estimated that 15,000-20,000 new cases of ONFH are diagnosed in the US each year [7]. The incidence of ONFH is increasing, and more patients with ONFH are now diagnosed in the clinic [8,9].…”
Section: Introductionmentioning
confidence: 99%